Brand and Price Advertising in Online Markets - Baye, Michael R.; Morgan, John (Management Science, 2009)
We model an environment where e-retailers sell similar products and endogenously engage in both brand advertising (to create loyal customers) and price advertising (to attract “shoppers”). In contrast to models where loyalty is exogenous, endogenizing the creation of loyal customers by allowing firms to engage in brand advertising leads to a continuum of symmetric equilibria; however, there is a unique equilibrium in secure strategies, and the set of equilibria converges to this unique equilibrium as the number of potential e-retailers grows arbitrarily large. Price dispersion is a key feature of all of these equilibria, including the limit equilibrium. Branding tightens the range of prices and reduces the value of the price information provided by a comparison site, and this reduces profits for platforms (such as an Internet price comparison site) where firms advertise prices. Data from a leading price comparison site are shown to be consistent with several predictions of the model.